Correction: Haddad et al. Evaluation of the Antibacterial Activity of New Dermaseptin Derivatives against Acinetobacter baumannii. Pharmaceuticals 2024, 17, 171 - Houda Haddad; Radhia Mejri; Amira Zaïri (MDPI AG, 2024)
Removal of an Author [...]